DETERMINATION OF PRIORITY FOR ROAD INFRASTRUCTURE QUANTITY DEVELOPMENT IN SUPPORTING REGIONAL DEVELOPMENT IN KENDARI CITY WITH PROCESS HIERARCHY ANALYSIS METHOD - Waode Anggun Mahrani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The high level of activity in Kendari city is due to its status as the provincial capital with functions as the center of government, education, and economic activity, resulting in limited road space, low accessibility and traffic congestion. The government's desire to make Kendari city a service city and attractive to investors and tourists, both domestic and foreign. In order to meet the needs of the community, with limited local government resources to meet them in a short period of time, it is necessary to do optimization. This research aims to: 1) analyze criteria and weights in determining road development priorities; 2) determine road development priorities in supporting regional development; 3) measure the impact of road development projects on relevant key performance indexes. The data analysis method is descriptive quantitative and qualitative with hierarchical analysis process (AHP). The results of the study concluded 1) The weighting analysis shows in order of the highest weight criteria accessibility, benefits, road network performance, regional development and costs. 2) Hierarchical process analysis shows that the most priority alternative chosen to meet the needs of the road network is a combination of Kendari ring road and inner ring road 3) Both combinations are useful for increasing accessibility, improving the performance of the existing road network, becoming a strategic road to support the industrial sector, trade and urban growth centers in order to improve the regional economy.